Explanation beyond causation? New directions in the philosophy of scientific explanation. Issue 2 (February 2017) - Reutlinger, Alexander
Abstract: In this paper, I aim to provide access to the current debate on non‐causal explanations in philosophy of science. I will first present examples of non‐causal explanations in the sciences. Then, I will outline three alternative approaches to non‐causal explanations – that is, causal reductionism, pluralism, and monism – and, corresponding to these three approaches, different strategies for distinguishing between causal and non‐causal explanation. Finally, I will raise questions for future research on non‐causal explanations.